Implementation of virtual reality in technical education - an innovative view - Shamsuzzoha, Ahm; Al-Kindi, Mahmood; Kankaanpaa, Timo (Inderscience, 2020)
Advancement of Virtual Reality (VR) is creating many opportunities to efficiently managing educational system in the present days. The application of VR in educational sector can contribute towards to cope up with today's digitalised educational management system. To keep such objective in mind, this research study investigated the possibility to apply VR in education, especially in technical education and analysed its potential outcomes. The inherent benefits of VR in technical education are elaborated within the scope of this research study with the aim to meet the expectation of today's up-to-date student generation. A case study on the application of VR is conducted to demonstrate how the innovative technology can be employed to produce creative training and learning engineering curriculum. Overall outcomes from this case example are presented along with the various works done by the researchers and practitioners on virtual reality are reviewed and highlighted as well.
Keywords: 3D visualization; case study; management of education; technical education; virtual reality; innovations; fi=Tuotantotalous|en=Industrial Management|